Oral creatine supplementation attenuates muscle loss caused by limb immobilization: a systematic review - Camila Souza Padilha; Paola Sanches Cella; Leo Rodrigues Salles; Rafael Deminice
Abstract Introduction: Recent studies have pointing creatine supplementation as a promising therapeutic alterna- tive in several diseases, especially myopathies and neurodegenerative disorder. Objective: elucidate the role of creatine supplementation on deleterious effect caused by limb immobilization in humans and rats. Methods: Analyzed articles were searched by three online databases, PubMed, SportDicus e Scielo. After a review and analysis, the studies were included in this review articles on effect of creatine supplementation on skeletal muscle in humans and rat, before, during and after a period of limb immobilization. Results: Studies analyzed demonstrated positive points in use of creatine supplementation as a therapeutic tool to mitigating the deleterious effects of limb immobilization, in humans and rat. Conclusion: The dataset of this literature review allows us to conclude that creatine supplementation may reduce muscle loss and/or assist in the recovery of muscle atrophy caused by immobilization and disuse in rats and humans. Also, we note that further research with better methodological rigor is needed to clarify the mechanisms by which creatine support the recovery of muscle atrophy. Moreover, these effects are positive and promising in the field of muscle rehabilitation, especially after member's immobilization.